Agri-Food Quality II : quality management of fruits and vegetables - Hagg, M. (Special publication ;, 1999)
As consumer demand for high quality products grows, the quality of our food is increasingly under the spotlight. Agri-food quality II addresses the quality management of plant-based food materials throughout the production chain, from field to table. Developments relating to the improvement of vegetable and fruit quality through plant breeding, genetic manipulation, modification of cultivation technology and optimisation of harvesting and storage techniques, are covered in detail. Furthermore, the concept of functional foods and sustainable production are also discussed. With contributors from international experts, Agri-food quality II will be of great interest to food scientists, agriculturalists, or indeed anyone involved with part of the food chain, both in academia and industry.